2020
DOI: 10.1101/2020.01.30.926642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perfluorooctanoic acid activates multiple nuclear receptor pathways and skews expression of genes regulating cholesterol homeostasis in liver of humanized PPARα mice fed an American diet

Abstract: Humans are exposed to per-and polyfluoroalkyl substances (PFAS) in their drinking water, food, air, dust in their homes, and by direct use of consumer products. Increased concentrations of serum total cholesterol and low density lipoprotein cholesterol are among the endpoints best supported by epidemiology. The objectives of this study were to generate a new model for examining PFAS-induced dyslipidemia and to conduct molecular studies to better define mechanism(s) of action. We tested the hypothesis that PFOA… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“…This is seen by lower increase in transcripts and protein levels of PPARa target genes (Nakamura et al 2009;Nakagawa et al 2012). Still, in combination with these gene expression changes, PFOA-treated hPPARa mice showed increased lipid accumulation in liver (Nakagawa et al 2012;Schlezinger et al 2020). Actually, despite the reduced responsiveness of hPPARa to PFOA, hPPARa mice appeared to be substantially more susceptible to liver steatosis than the WT mice, as shown by larger increases in hepatic TG levels (Nakagawa et al 2012).…”
Section: Are Ppara-mediated Effects In Rodents Relevant For Human Health?mentioning
confidence: 98%
See 2 more Smart Citations
“…This is seen by lower increase in transcripts and protein levels of PPARa target genes (Nakamura et al 2009;Nakagawa et al 2012). Still, in combination with these gene expression changes, PFOA-treated hPPARa mice showed increased lipid accumulation in liver (Nakagawa et al 2012;Schlezinger et al 2020). Actually, despite the reduced responsiveness of hPPARa to PFOA, hPPARa mice appeared to be substantially more susceptible to liver steatosis than the WT mice, as shown by larger increases in hepatic TG levels (Nakagawa et al 2012).…”
Section: Are Ppara-mediated Effects In Rodents Relevant For Human Health?mentioning
confidence: 98%
“…In parallel to the hypolipidemic effects in the blood, other lipid disturbances observed include enhanced intrahepatic accumulation of lipids, mainly TGs, in rodents for both PFOS (Bijland et al 2011;Wan et al 2012;Wang et al 2014), and PFOA (Nakagawa et al 2012;Tan et al 2013;Wang et al 2013;Das et al 2017;Hui et al 2017;Wu et al 2018;Schlezinger et al 2020) (see Table 2 for examples). The liver appears to be a major target organ for both compounds in rats and mice, as indicated by increased liver weight, hypertrophy of centrilobular hepatocytes, induction of peroxisomal and mitochondrial ß-oxidation, and in some cases necrosis.…”
Section: Effects Observed In Animal Toxicity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging animal toxicology and histology and human population data provide mechanistic clues that PFAS disrupt hepatic metabolism, leading to increased bile acid reuptake and lipid accumulation in liver (Salihovic et al 2020; Schlezinger et al 2020). A review of NAFLD and toxicant exposure concluded that PFAS are associated with early steatosis (“fatty liver”), the preclinical stage of NAFLD (Armstrong and Guo 2019).…”
Section: Current Knowledge Of Pfas Toxicity In Humansmentioning
confidence: 99%
“…Human PFAS lipid findings may be related to experimental findings of induced adipogenesis, impaired bile acid metabolism/synthesis, strongly decreased CYP7A1 enzyme activity, altered fatty acid transport, and intracellular lipid accumulation with steatosis, including in PPAR‐α‐null or PPAR‐α‐humanized animals (Guruge et al 2006; Lau et al 2007; Bijland et al 2011; Bjork et al 2011; Wang et al 2014; Filgo et al 2015; Das et al 2017; Salihovic et al 2019; Zhang et al 2019; Behr et al 2020a; Liu S et al 2020b; Schlezinger et al 2020). Independent of PFAS exposure, similar alterations in metabolic pathways have been related to disrupted fatty acid beta‐oxidation and increased free cholesterol in toxicology studies (Perla et al 2017).…”
Section: Current Knowledge Of Pfas Toxicity In Humansmentioning
confidence: 99%